Permanent Magnet Generator Design With Stable Output Under Variable Speed: Desain Generator Magnet Permanen dengan Output Stabil pada Kecepatan Variabel - Mochamad Aldhy Saputro Alamsyah; A’rasy Fahruddin; Mulyadi; Edi Widodo (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Electrical energy demand continues to increase, requiring reliable generation systems with efficient performance. Specific Background: Permanent magnet synchronous generators are widely used due to their simplicity and ability to operate at low speeds. Knowledge Gap: Previous studies have not fully explored optimal design parameters for achieving stable output under varying rotational conditions. Aims: This study aims to design and analyze a permanent magnet generator to evaluate its electrical output characteristics. Results: The generator produces measurable voltage, current, and power under different rotational speeds, demonstrating consistent performance trends across testing conditions. The output increases proportionally with rotational speed, indicating stable operational behavior. Novelty: The study presents a practical implementation of generator design with systematic testing under variable speed conditions. Implications: The results provide a reference for developing small-scale power generation systems with stable electrical output for various applications. Keywords: Permanent Magnet Generator, Electrical Energy, Generator Design, Output Voltage, Rotational Speed Key Findings Highlights Electrical output shows proportional relationship with rotational variation System testing confirms consistent behavior across multiple operating conditions Prototype demonstrates feasibility for small scale energy conversion applications